TRINEXAPAC-ETHYL AFFECTS GROWTH AND GAS EXCHANGE OF UPLAND RICE - Alvarez, Rita De Cassia FÉlix; Crusciol, Carlos Alexandre Costa; Nascente, Adriano Stephan; Rodrigues, JoÃo Domingos; Habermann, Gustavo; Neto, Vespasiano Borges De Paiva (Universidade Federal Rural do Semi-Árido, 2016)
ABSTRACT: A major problem affecting some upland rice cultivars is the increase in plant size when subjected to high doses of nitrogen fertilizer, leading to high levels of lodging. A method to reduce the height of upland rice, and therefore lodging, would be to use plant growth regulators. However, little information exists on the effect of these regulators on plant physiological processes. Therefore, the objective of this study was to evaluate the influence of trinexapac-ethyl application in upland rice via analysis of growth and gas exchange. The experiment was carried out under greenhouse conditions using the BRS Primavera cultivar. A completely randomized design with eight replications was used. Treatments were carried out with and without the application of the plant growth regulator, and plants were subject to two-stage assessments in which physiological and gas-exchange indices were measured. The use of trinexapac-ethyl improved the growth of rice plants from the flowering to the physiological maturity stage, resulting in higher values of leaf area ratio, specific leaf area, and leaf matter ratio in treated plants. At the same time, it provided smaller reduction in net CO2 assimilation at the physiological maturity stage. Thus, net/apparent assimilation rate did not change after the application of growth regulator, but relative growth rate decreased in these treated plants. These results indicate the occurrence of self-shading in rice plants induced by what might be a supra-optimum trinexapac-ethyl concentration.

RESUMO: Um dos grandes problemas de alguns cultivares de arroz de terras altas é o aumento do porte da planta quando submetido a altas doses de fertilizante nitrogenado, atingindo altos índices de acamamento. Uma opção para diminuir a altura das plantas de arroz, e com isso também o acamamento, seria a utilização de reguladores vegetais, entretanto, existem poucas informações sobre o efeito desses reguladores nos processos fisiológicos da planta. Assim, objetivou-se, por meio da análise de crescimento e de trocas gasosas, avaliar a influência da aplicação de etil-trinexapac na cultura do arroz de terras altas. O experimento foi conduzido em casa-de-vegetação usando-se a cultivar BRS Primavera. Foi utilizado o delineamento experimental inteiramente casualizado, com oito repetições. Os tratamentos foram constituídos sem e com aplicação de regulador de crescimento vegetal e dois estádios de desenvolvimento avaliados. Foram estimados os índices fisiológicos e trocas gasosas. O uso de regulador de crescimento etil-trinexapac proporcionou melhor desenvolvimento das plantas de arroz do estádio de florescimento a maturação fisiológica, resultando em valores de RAF, AFE e PMF mais elevados nas plantas tratadas. Paralelamente, proporcionou menor redução na assimilação líquida de CO2 na fase de maturação fisiológica. Assim, a TAL não sofreu alteração em função do regulador de crescimento e a TCR apresentou redução nas plantas tratadas. Estes resultados indicam a ocorrência de autosombreamento na cultura induzida pela concentração do etil-trinexapac, que pode ter sido supra ótima.
ETIL-TRINEXAPAC AFETANDO O CRESCIMENTO E AS TROCAS GASOSAS DO ARROZ DE TERRAS ALTAS
Keywords: Oryza sativa; Growth regulator; Physiological process; Oryza sativa; Regulador de crescimento; Processo fisiológico